Gude & godlie ballatis noted - Duffin, Ross W. 1951- (A-R Editions, Inc., 2022)
"One of the monuments of mid-sixteenth-century Scottish letters is the Ane Compendious Buke of Godlye Psalmes and Spirituall sangis, also known simply as the Gude & Godlie Ballatis, first published in Edinburgh in 1565 and reprinted for decades afterwards. Although a few secular tunes, like "Go from my window" and "John come kiss me now," are inferred in the volume through the use of poetic parodies, well over a hundred of the collection's self-described 'sangis' give no musical direction whatsoever. A half-century ago, Helena Mennie Shire questioned whether the GGB's music could be properly recovered, thereby reclaiming it "as a book of versions intended for singing." Using contrafacta from the early Lutheran repertoire, from Coverdale's Goostly Psalmes of 1535, and particularly the Forme of Prayers (the Scottish psalter) of 1564, this edition presents tunes and lyrics for all of the songs in the corrected GGB edition of 1578, uniquely preserved at the Huntington Library in San Marino, California." --
"The collection is often attributed to the Wedderburn brothers, John, James, and Robert, though there is nothing definitive to make that connection." - Page xiii
Keywords: Hymns / Scotland / Scores; Psalms (Music) / Scotland / Scores; Hymns, German / Translations into Scots; Hymns, English / Translations into Scots; Hymn tunes; Hymns, English; Hymns, German; Hymns / Scores; Scotland; Sacred music; Scores